Determinants of Burnout Among Healthcare Professionals Working in the Labour Room of a Tertiary Care Hospital in South Punjab, Pakistan - Sadia Zahoor; Mamoona Zahoor; Faiza Javed; Mahwish Najam; Shahida Aslam; Iffat Yasmeen (Pakistan Armed Forces Medical Journal, 2023)
Objective: To find out the frequency and determinants of burnout among healthcare workers and staff working in a labour room of a Gynaecology unit of a tertiary care hospital in South Punjab, Pakistan.